2019
DOI: 10.1177/1558944719851192
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Interosseous Nerve Palsy After Shoulder Arthroscopy Treated With Surgical Decompression: A Case Series and Systematic Review of the Literature

Abstract: Background: Anterior interosseous nerve (AIN) palsy is a very uncommon cause of upper extremity pain and weakness that comprises less than 1% of all upper extremity nerve palsies. Rarely reported but also mentioned in the literature is AIN palsy after shoulder arthroscopy. Methods: A systematic review of the literature to date using PubMed was conducted to identify patients who suffered AIN palsy after shoulder arthroscopy procedures. Articles included met the following criteria: (1) published in English; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Anterior interosseous nerve neuropathy after shoulder arthroscopy is not a well-established complication but is becoming increasingly recognized. To our knowledge, there are currently 16 reported cases of AIN neuropathy after shoulder arthroscopy in the literature, which includes the previously mentioned case report 5–9 . The potential etiologies for this condition, diagnostic workup, and management strategies are reviewed hereinafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior interosseous nerve neuropathy after shoulder arthroscopy is not a well-established complication but is becoming increasingly recognized. To our knowledge, there are currently 16 reported cases of AIN neuropathy after shoulder arthroscopy in the literature, which includes the previously mentioned case report 5–9 . The potential etiologies for this condition, diagnostic workup, and management strategies are reviewed hereinafter.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are currently 16 reported cases of AIN neuropathy after shoulder arthroscopy in the literature, which includes the previously mentioned case report. [5][6][7][8][9] The potential etiologies for this condition, diagnostic workup, and management strategies are reviewed hereinafter.…”
Section: Discussionmentioning
confidence: 99%
“…Boardman et al 25 demonstrated that mechanical nerve injury, such as damage to the musculocutaneous nerve, during rotator cuff repairs occurs in 1% to 2% of patients. A systematic review by Nammour et al 26 also demonstrated anterior interosseous nerve palsy to be a rare but a possible result of shoulder arthroscopy secondary to mechanical trauma, compressive hematoma, and anesthetic neurotoxicity. Nerve injuries can also occur secondary to patient positioning during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Prodromal pain in the shoulder, arm, or elbow may be present. The aetiologies of anatomical compression, physical exertion, repetitive activity, infection, vaccination, pregnancy, supracondylar humerus fracture on children, sleeping on an arm, forearm immobilization, and surgery unrelated to AIN (e.g., shoulder arthroscopy) have been described, but sometimes there is no apparent cause [ 18 , 33 , 35 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Clinical Presentationmentioning
confidence: 99%